2022
DOI: 10.1242/dev.199826
|View full text |Cite
|
Sign up to set email alerts
|

Pthlha and mechanical force control early patterning of growth zones in the zebrafish craniofacial skeleton

Abstract: Secreted signals in patterning systems often induce repressive signals that shape their distributions in space and time. In developing growth plates (GPs) of endochondral long bones, Parathyroid hormone-like hormone (Pthlh) inhibits Indian hedgehog (Ihh) to form a negative feedback loop that controls GP progression and bone size. Whether similar systems operate in other bones and how they arise during embryogenesis remain unclear. We show that Pthlha expression in the zebrafish craniofacial skeleton precedes c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 91 publications
0
14
0
Order By: Relevance
“…The Ihh-Pthlh feedback loop appears to be conserved in mammalian cranial base synchondroses, although Pthlh is expressed throughout the RZ and PZ ( 94 , 95 ). A few studies in zebrafish have shown the conservation of GZ patterning mechanisms between teleost fish and mammals ( 45 , 96 ), and an earlier onset of Pthlha expression than previously described, namely at the onset of chondrogenesis and before the onset of ihha expression ( Figure 5B ) ( 46 ). Novel findings in zebrafish have also shown the potential of this model for expanding our understanding of GZ patterning, as they suggest that the Ihh-Pthlh feedback loop maintains but does not establish the GZ pattern, at least in some pharyngeal endochondral bones ( 46 ).…”
Section: Development and Cellular Architecture Of Endochondral Growth...mentioning
confidence: 74%
See 3 more Smart Citations
“…The Ihh-Pthlh feedback loop appears to be conserved in mammalian cranial base synchondroses, although Pthlh is expressed throughout the RZ and PZ ( 94 , 95 ). A few studies in zebrafish have shown the conservation of GZ patterning mechanisms between teleost fish and mammals ( 45 , 96 ), and an earlier onset of Pthlha expression than previously described, namely at the onset of chondrogenesis and before the onset of ihha expression ( Figure 5B ) ( 46 ). Novel findings in zebrafish have also shown the potential of this model for expanding our understanding of GZ patterning, as they suggest that the Ihh-Pthlh feedback loop maintains but does not establish the GZ pattern, at least in some pharyngeal endochondral bones ( 46 ).…”
Section: Development and Cellular Architecture Of Endochondral Growth...mentioning
confidence: 74%
“…A few studies in zebrafish have shown the conservation of GZ patterning mechanisms between teleost fish and mammals ( 45 , 96 ), and an earlier onset of Pthlha expression than previously described, namely at the onset of chondrogenesis and before the onset of ihha expression ( Figure 5B ) ( 46 ). Novel findings in zebrafish have also shown the potential of this model for expanding our understanding of GZ patterning, as they suggest that the Ihh-Pthlh feedback loop maintains but does not establish the GZ pattern, at least in some pharyngeal endochondral bones ( 46 ). Instead, the zebrafish Pthlh ortholog, pthlha , and mechanical force from muscle contraction initiate the HZ and the location of subsequent ihha expression, thereby establishing the negative feedback-loop that maintains GZs ( Figure 5B ) ( 46 ).…”
Section: Development and Cellular Architecture Of Endochondral Growth...mentioning
confidence: 74%
See 2 more Smart Citations
“…This feedback loop is largely conserved in cranial base synchondroses, although Pthlh is expressed throughout the RZ and PZ 25,26 . In zebrafish this feedback loop is also initiated at the onset of chondrogenesis in the ceratohyal cartilages, prefiguring the location and presumably the size of the future GZ 27 . Possible molecular mechanisms mediating PZ size variation in cichlids include changes in Ihh and/or Pthlh expression levels as well as those of their activators or repressors.…”
Section: Discussionmentioning
confidence: 99%